The Implementation of Character Building through Living Values Education in the English Language Course Program at Mahima Institute Indonesia, Bali. - Nyoman Canestra Adi Putra (Jurnal Penelitian Mahasiswa Indonesia, 2023)
Education is an essential aspect to get success in this competitive world. Sadly, the education world was shocked by numerous negative incidents happening in public schools around the globe, such as physical violence, gun violence, drug abuse and psychological bullying. One of the solutions to this problem is to give character education by implementing Living Values Education (LVE) in schools. In Mahima Institute Indonesia, an English Language Course in Bali, LVE is applied to embed living values in students’ character. There are twelve values taught to students, namely peace, love, respect, responsibility, tolerance, honesty, humility, happiness, cooperation, simplicity, freedom and unity. These values are embedded in many activities in classroom through songs, games, projects and other activities. This study utilized qualitative research approach. Meanwhile, the research method is a case study. The data collection techniques were in the form of interviews, observation, and documentation. The data analysis techniques were carried out through data reduction, data presentation, and verification. The results of the study show that LVE provide opportunities to students to explore more about values and why it is important. LVE also creates a positive learning environment in classroom and teach the students how to be respectful, care for each other while having fun in classroom. Therefore, the students learn not only academically, but also characters.